ESG Performance and AI Governance: Evidence from Thailand - Moolkham, Mongkhol (International Journal of Energy Economics and Policy, 2026)
This study examines how environmental, social, and governance (ESG) performance affects artificial intelligence (AI) governance. Using panel data from companies listed on the Stock Exchange of Thailand, this study employs ordinary least squares regression to test the hypothesis. The findings suggest that ESG performance has a significant positive association with AI governance, supporting the notion that ESG-related capabilities in compliance, transparency, and stakeholder engagement can be used as an internal governance framework for mitigating emerging AI-related risks. However, this translation is not automatic but depends critically on leadership. The positive moderating effects of Gen X and Gen Y CEOs, contrasted with the insignificant and negative moderation observed for Baby Boomer CEOs, suggest that younger leaders—who are generally more digitally oriented—are better able to convert ESG commitments into concrete AI policies, controls, and oversight mechanisms. Overall, the findings reveal a dual governance structure wherein ESG performance serves as the foundational "hardware" for responsible AI, while the generational characteristics of CEOs act as the "software" that influences the efficacy of leveraging these ESG capabilities to establish and maintain AI governance.